PENDEKATAN PERILAKU TRENGGILING SUNDA DALAM PERANCANGAN PUSAT KONSERVASI - Nur Afifah Khairunnisa; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2021)
Indonesia is a country with the second highest mega-biodiversity in the world. However, it is also known as the country that has the largest list of critically endangered-protected animals based on the International Union for Conservation of Nature (IUCN) category. This is due to the lack of protection and lack of public knowledge and awareness. The relationship between living organisms is, as a matter of fact very important in the ecosystem. Thus, principles or ways of thinking are needed in the attempts of preserving natural resources to ensure a sustainable life, which are called Beyond Ecology. At the time being, several animals in Indonesia have reached the brink of extinction, one of them being the Sunda pangolin (Manis Javanica), whose population has decreased up to 80% in the last 21 years due to poaching and illegal trading. One of the efforts of preservation is to design a conservation center combined with educational and recreational programs, with the aim of protecting, restoring, and maintaining the safety of the Sunda Pangolin as well as increasing the sense of care, public awareness and knowledge of the community on the importance of biodiversity in life. By using the analogy method, it is necessary to analyze the behavior and characteristics of the Sunda pangolin in the design concept of the conservation center to produce a design that is well-suited to the needs of the Sunda pangolin and the Indonesian people. Keywords: conservation; education; ecology; recreation; sunda pangolinAbstrakIndonesia merupakan negara megabiodiversitas peringkat kedua paling tinggi di dunia. Namun, dikenal juga sebagai negara yang memiliki daftar terbanyak mengenai satwa lindung yang terancam punah berdasarkan kategori International Union for Conservation of Nature (IUCN). Hal ini dikarenakan kurangnya perlindungan, lemahnya peraturan, dan minimnya wawasan serta kesadaran masyarakat. Padahal, relasi antar organisme hidup sangat penting dalam ekosistem. Sehingga, diperlukannya prinsip atau pemikiran dalam mengupayakan terpeliharanya sumber daya alam yang disebut Beyond Ecology untuk menjamin kehidupan yang berkelanjutan. Kini, beberapa hewan di Indonesia telah mencapai ambang kepunahan, salah satunya adalah trenggiling sunda (Manis Javanica) yang populasinya menurun hingga 80% dalam kurun waktu 21 tahun terakhir dikarenakan perburuan liar dan perdagangan ilegal. Salah satu upaya pelestariannya adalah melakukan perancangan konservasi yang digabung dengan program edukasi dan rekreasi, dengan tujuan melindungi, memulihkan, dan melestarikan keberadaan trenggiling sunda sekaligus meningkatkan rasa kepedulian, kesadaran dan wawasan masyarakat akan pentingnya pelestarian keanekaragaman hayati dalam kehidupan. Dengan menggunakan metode analogi, diperlukannya analisis pendekatan perilaku dan karakteristik trenggiling sunda dalam konsep perancangan pusat konservasi sehingga menghasilkan perancangan yang sesuai dengan kebutuhan trenggiling sunda dan masyarakat Indonesia.